Spatial Distribution of Educational Services in the City of Umm Qasr for the Academic Year (2023-2024) - Assist. Lect . Saja Abdullah Jaloub , Assist. Lect . Saja (Basra studies journal, 2026)
The research aims to identify the reality and efficiency of the spatial distribution of educational services in the city of Umm Qasr for the academic year (2023-2024) compared to the size of population there. The study showed the presence of (45) educational institutions, including (34) government institutions and (11) private institutions, which formed a phase Kindergartens accounted for (9.8%) of the size of educational institutions, while the percentage of primary schools reached (60%) of the total number of educational institutions. The intermediate school also recorded a percentage of (9.8%) of the number of educational institutions, they constituted a percentage of (4.4%) of the total educational institutions, while the secondary stage constituted a percentage of (8.17%) of the total educational institutions throughout the city of Umm Qasr. Services were distributed differently among the neighborhoods of the city of Umm Qasr through using the map. The distribution of these various types of services will help us diagnose the shortcomings and defects in distribution If any, its efficiency will be studied in terms of the extent to which it meets the needs of the city’s residents and is compatible with their numbers and density within the city’s residential neighborhoods, As defined in the field of distributional research where a specific place is defined educationally and several widely dispersed groups are not researched and work is done from the research level.